Respuesta :
Multiply the first equation by 3 and the second equation by 2:
[tex]\begin{cases}6x-9y=27\\6x+10y=8\end{cases}[/tex]
Subtract the two equation to get rid of the x variable:
[tex]-9y-10y=27-8 \iff -19y = 19 \iff y = -1[/tex]
Use the value of y to determine the value of x: for example, using the first equation we have
[tex] 2x+3=9 \iff 2x=6 \iff x=3 [/tex]
Answer:
x = 3 and y = -1 ⇒ (3, -1)
Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}2x-3y=9&\text{multiply both sides by 5}\\3x+5y=4&\text{multiply both sides by 3}\end{array}\right\\\\\underline{+\left\{\begin{array}{ccc}10x-15y=45\\9x+15y=12\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad19x=57\qquad\text{divide both sides by 19}\\.\qquad x=3\\\\\text{Put the value of x to the second equation:}\\\\3(3)+5y=4\\9+5y=4\qquad\text{subtract 9 from both sides}\\5y=-5\qquad\text{divide both sides by 5}\\y=-1[/tex]